Handling Radicalism and Intolerance Practices is Just a Discourse - Josep Tatang; Victor Deak; Joko Prihanto (INTERNATIONAL JOURNAL OF SOCIAL, POLICY AND LAW, 2021)
Indonesian is a great nation, a nation that is rich and plentiful with its natural resources. The Indonesian nation is very rich in traditions and various cultural and religious backgrounds, all of which are united in the formulation of Pancasila (The Five Principles). With the formulation of Pancasila, it is hoped that all Indonesian citizens will have a strong sense of unity, have high nationalism and tolerance. But it cannot be denied that the formulation of Pancasila is only a utopian ideal and it can be assumed that it is only a discourse for momentary interests. The purpose of this paper is to provide information about the nationalism praxis that occurs in the nation and provide solutions on how to protect the integrity of the nation and state from conflicts between groups that would lead to divide national unity. In this paper, the author provides clear information on the practice of legal injustice and the practice of nationalism that occurs in Indonesia. Indonesia needs to learn more from other countries how they uphold justice and unite differences in religion, ethnicity and race as their own strength.